2012
DOI: 10.1024/0040-5930/a000281
|View full text |Cite
|
Sign up to set email alerts
|

Hausstaubmilbenallergie

Abstract: House dust mites can be found all over the world where human beings live independent from the climate. Proteins from the gastrointestinal tract- almost all known as enzymes - are the allergens which induce chronic allergic diseases. The inhalation of small amounts of allergens on a regular base all night leads to a slow beginning of the disease with chronically stuffed nose and an exercise induced asthma which later on persists. House dust mites grow well in a humid climate - this can be in well isolated dwell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…It is estimated that the annual morbidity and mortality rates have been increasing in recent years worldwide. According to a report by the World Health Organization, >80% of asthma in children results from an allergic reaction in which the house dust mite (HDM) is the major pathogen (1). Inhaled corticosteroids (ICSs) and specific immunotherapy (SIT) are widely used inflammatory treatments for controlling the symptoms of asthma (2).…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that the annual morbidity and mortality rates have been increasing in recent years worldwide. According to a report by the World Health Organization, >80% of asthma in children results from an allergic reaction in which the house dust mite (HDM) is the major pathogen (1). Inhaled corticosteroids (ICSs) and specific immunotherapy (SIT) are widely used inflammatory treatments for controlling the symptoms of asthma (2).…”
Section: Introductionmentioning
confidence: 99%
“…Another option is to place the stuffed animals in a pillowcase or laundry bag and wash them in hot water, preferably at temperatures above 130 • F (54 • C), on a regular basis. Alternatively, they can be placed in a plastic bag and stored in the freezer for 24 h. After either method, one should make sure to thoroughly dry the stuffed animals, either by air-drying them or using a hot dryer [30].…”
Section: Environmental Modificationsmentioning
confidence: 99%
“…Furthermore, UV radiation has been associated with the development of eczema and food allergies [ 8 , 9 ]. Additionally, the tropical and humid environments, indoor dust mites facilitate to breed, and dust mites, which are often the trigger of allergic diseases such as allergic rhinitis and asthma [ 10 , 11 ]. Many studies have confirmed that exposure to PM 10 , PM 2.5 , NO 2 , CO, and O 3 , can deteriorate respiratory diseases [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%